The Heat's On - Ratoff, Gregory; Planer, Frank; West, Mae; Moore, Victor; Gaxton, William (Sony Pictures, 2005)
Screen siren Mae West took a 27 year break after this movie. Though she did write her own dialogue here, she had almost no control over the rest of this uneven musical production. She plays an actress involved in several Broadway shows at once. [movies.go.com]
Keywords: DVD-Video